Od spekulatywnego humoryzmu do eksperymentalnego fizjologizmu - Drozdowicz, Zbigniew (Humaniora. Czasopismo Internetowe, 2021)
Pointing out the boundary after crossing which physiology of man stops being pseudoscience and becomes true science had been a task undertaken for a long time. Some of those attempts caused a greater and some a lesser reservation. Relatively limited ways of recognizing life processes, including the preveiling for centuries ban of doing autopsy, on many occasions opened widely a door for various pseudo and quasi scientific speculations. Numerous of them had survived through the centuries. Although with time passing by it had been proved that some of them a scientifically groundless they had been replaced with new ones. In my remarks I recall the example of speculative humourism as well several examples of experimental physiologism, including behaviorism which is still popular in science. Certainly, more of such examples can be given at any time. We cannot say however that diverse pseudoscientific speculations in physiology have been eradicated. We might say that today we are given a much smaller space for speculativism in that or other areas of biological research.